Some experimental and theoretical investigations on fire retardant coir/epoxy micro-composites - Misra R.K.; Kumar S.; Sandeep K.; Misra A. (My University, 2025)
This article reports some experimental and theoretical investigations on fire retardant coir/epoxy micro-composites. The coir fiber is treated with saturated bromine water for increasing the electrical properties and then mixed with stannous chloride solution for improving the fire retardant properties. Only 5% (approximately) of fire retardant filler reduces the smoke density by 25% and the LOI value increases to 24%. The mechanical properties of the coir/epoxy micro-composites are not affected much after incorporation of filler. Flexural strength and flexural modulus of the NET increases tremendously compared to NEU and NE. Multiquadric radial basis function (MQRBF) method is applied for static and dynamic analysis of coir/epoxy micro-composite plate under uniformly distributed load. Damping behavior and natural frequencies are observed in NE, NEU, and NET. MQRBF is applied for spatial discretization and Newmark implicit scheme is used for temporal discretization. The discretization of the differential equations generates greater number of algebraic equations than the unknown coefficients. The multiple linear regression analysis, which is based on the least square error norm, is employed to obtain the coefficients. Simple supported and clamped boundary conditions are considered for verification of present results and they are compared with other existing analytical methods. © SAGE Publications 2008.